A novel NH2-MIL-125/dandelion-like MnO2 nanosphere composite with a rapid interfacial electron transfer pathway for photocatalytic degradation of ornidazole - Patial, Shilpa; Kumar, Rohit; Sudhaik, Anita; Sonu; Thakur, Sourbh; Kumar, Naveen; Ahamad, Tansir; Kaya, Savas; Hussain, Chaudhery Mustansar; Singh, Pardeep; Raizada, Pankaj (Solid state sciences, 2024)
The effectiveness of photocatalysis is constrained by the insufficient efficiency of charge separation, migration, and utilization that are generated by light. Enhanced photocatalytic efficiency is significantly achieved through the important technique of integrating Metal-Organic Frameworks (MOFs) with other materials to form heterojunction structures. In this study, NH2-MIL-125/MnO2 (NMM) composite photocatalyst has been designed, featuring a Z-scheme heterojunction structure with enhanced interfacial charge transfer and an improved lifetime of charges. The physicochemical properties of the NMM composite were analysed by multiple techniques. The photocatalytic efficiency of the NMM composite is notably superior to pristine NH2-MIL-125 and MnO2. This enhanced performance can be credited to the improvement in the recombination rate, charge transfer resistance, and adsorption site, as revealed by the characterization data. The photocatalytic performance of the NMM composite was analysed for ornidazole antibiotics degradation, which showed 91.31 % degradation efficiency at optimum conditions. In the photocatalytic degradation mechanism, •O2− free radicals were the major oxidative species responsible for the ornidazole degradation. [Display omitted] •NH2-MIL-125/MnO2 photocatalyst constructed by hydrothermal method.•Incorporation of MnO2 with NH2-MIL-125 for improved photocatalytic activity.•Increase in specific surface area due to heterojunction formation.•Z-scheme heterojunction formation improved the charge dynamics.•NH2-MIL-125/MnO2 photocatalyst showed 91.31 % degradation efficiency for ornidazole.